An observational, prospective study of monthly adalimumab therapy for disease maintenance in psoriasis patients: a possible new therapeutic option for good responders to the initial induction treatment. (15th June 2012) - Taniguchi, T.; Noda, S.; Takahashi, N.; Yoshimura, H.; Mizuno, K.; Adachi, M.
Abstract Background While adalimumab is a mainstay of treatment for moderate to severe chronic plaque psoriasis, the data regarding optimal treatment intervals for therapeutic maintenance are limited. Objective We compared the clinical efficacy of biweekly maintenance administration of adalimumab with that of monthly treatment. Methods 17 psoriasis patients treated with adalimumab 40 mg every other week with initial loading dose of 80 mg until week 24 were assigned to the maintenance therapy with adalimumab 40 mg either every other week (n = 7), or every month (n = 10). The treatment efficacy was evaluated by the proportion of patients who achieved PASI 75 from the baseline at weeks 36, 48 and 60. There was no selection bias between the two groups. Results At week 24, all the patients except for one in each group achieved PASI 75. In both groups, all the patients who achieved PASI 75 at week 24 maintained PASI 75 responses at week 60. Regarding two patients who did not achieve PASI 75 at week 24, one biweekly treated patient experienced a gradual increase in therapeutic response while one monthly treated patient showed exacerbation after week 24. Conclusion Monthly adalimumab treatment seems to be a reasonable treatment option for patients who responded well to initial standard adalimumab treatment for 24 weeks. Since there are several limitations in this study, including the number of patients, observation period, and patients' characteristics, large randomized controlled trials are needed to confirm these results.